Efficacy of topical sucralfate vERSUs silver sulfadiazine in the management of burns: A 1-year randomized controlled trial - Godhi, AS (J West Afr Coll Surg, 2017)
BACKGROUND: Several medications and topical agents have been used for burn injuries. Among them, 1% silver sulfadiazine is the most commonly used topical agent for partial thickness burns. Recent studies have reported that the healing of burns is delayed by silver sulfadiazine. Search for the ideal topical agent for burn injuries is an ongoing research. The current study is undertaken with sucralfate as topical agent for dressing of burn injuries. AIM: To compare the efficacy of topical sucralfate with silver sulfadiazine in the healing of second degree superficial burns. STUDY DESIGN: A one-year randomized controlled trial SETTING: Department of General Surgery, JN Medical College and KLES Dr. Prabhakar Kore Hospital and Medical Research Centre, Belagavi, India METHODOLOGY: A total of 60 patients with < 50% second degree superficial burns were enrolled for the study. Patients were equally divided into two groups. Patients in group A were treated with topical sucralfate dressing and those in group B were treated with dressing. Demographics, history, physical, and systemic examinations of the patients were recorded. Routine blood investigations and culture and sensitivity were also performed. SPSS 20.0 was used for the analysis. RESULTS: In group A, the granulation appeared in less than 7 days in 15 (50%) patients, where as in group B, granulation appeared between 15 and 20 days in 17 (56.67%) patients (p = 0.149). The mean day of granulation was 8.11±3.92 days in group A compared to 8.93±3.29 days in group B (p = 0.396). The wound culture on day 1, 7 and 14 (p>0.050) did not differ significantly in both the groups. CONCLUSION: Overall, topical sucralfate dressing is efficacious in terms of development of early granulation in the healing of second-degree superficial burns compared to silver sulfadiazine dressing while antimicrobial effect is comparable to that of silver sulfadiazine dressing. It hastened burn wound healing process in second-degree superficial burns and should be used as an alternative agent or in combination with other topical agents. However, multicentric trials with bigger sample size are needed to strengthen the concept.